Mutually exclusive use of viral promoters in Epstein-Barr virus latently infected lymphocytes. - Woisetschlaeger, M (1989)
Of the eight viral antigens known to be expressed during Epstein-Barr virus latency, six are transcribed from a major rightward transcriptional unit, which gives rise to mRNAs containing common 5' exons. Analysis of cDNA clones has identified the use of two different promoters (Wp and Cp), located near the left-hand end of the viral genome, in generating these viral messages. Characterization of the activities of these two viral promoters in a number of Burkitt lymphoma and lymphoblastoid cell lines has revealed exclusive usage of only one of these promoters in all cell lines examined. Transfection of reporter constructs containing Wp and/or Cp linked to the bacterial chloramphenicol acetyltransferase gene into several different Epstein-Barr virus-infected cell lines generally supports a model in which the mutually exclusive use of Cp or Wp is determined by cellular factors and not by viral strain variation.